ER, PR, Cerb-B2, Ki-67, p53, Bcl-2, Cyclin-d1 Expressions in Invasive Breast Carcinomas and Comparison with the Clinical and Histopathological Parameters - Çelik, Özgür İlhan; Çelik, Serkan Yaşar; Dere, Yelda; Dere, Özcan; Özcan, Önder (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2018)
Aim:The aim of this study was to evaluate ER(Estrogen-receptor), PR(Progesteron-receptor), cerb-B2, ki-67, p53, Bcl-2(B cell lymphoma-2), Cyclin-D1 expressions in invasive breast carcinomas and compare them with the clinical and histopathological parameters. Methods: We analyzed 70 female patients retrospectively who underwent Modified Radical Mastectomy with Axillary lymph node dissection and were diagnosed as Invasive ductal carcinoma of the breast-Not otherwise specified at Mu?la S?tk? Koçman University, Faculty of Medicine, Department of Pathology between 2012 and 2016. ER, PR, cerb-B2, ki-67, p53, Bcl-2, Cyclin-D1 expressions of these tumors were obtained by immunohistochemistry. Clinical parameters of the patients were obtained from the hospital automation system.Results: Bcl-2; was found to be more positive in patients with young age, small and low-grade, ER/ PR-positive tumors without distant organ metastasis. However Bcl-2 negativity was found to be higher in p53, cerb-B2 positive and fastly-growing (tumors with high ki-67 index) tumors. Cyclin-D1; was found to be more positive in small and low-grade, slowly-growing (tumors with low ki-67 index), cerb-B2 and p53 negative tumors without vascular invasion and axillary lymph node metastasis. Conclusion: These results were interpreted as; Bcl-2 and Cyclin-D1 positivity were in favor of better outcome and better prognosis.